CHANGING TREND OF HOUSEHOLD FOOD CONSUMPTION: A CASE STUDY OF KOCHI, KERALA - Biju Abraham (SMART Journal of Business Management Studies, 2007)
Kerala, one of the southern states in India, is known for its consumerism. The development experiment of Kerala, which is popularly known as Kerala Model, indicates a higher level of consumption. In the recent years, there has been a mushrooming growth of the so-called Super Market or Margin Free Markets throughout the state. The city of Kochi is not an exception to this. These Super Markets are flooded with various kinds of materials, including food items which are ready to eat or can be eaten with minimal efforts. A study was conducted among 200 households in the City of Kochi with an objective to examine the consumption pattern of ready made food items by households. In the study, it was found that all the households under the study consumed these ready made food items. Though the consumption is not influenced by the number of members in the family, occupation and income, the choice of the type of product is determined mainly by the income level. The changing pattern of consumption not only provides more leisure time to women but will bring radical change in the market.